PENGARUH PENERAPAN STRATEGI THE FIRING LINE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 SOLOK SELATAN - Putri, Trionita Dwi (STKIP PGRI Sumbar, 2014)
The background of this research is the lack of students comprehension ofmathematical concept and the less of students responsible in learning. Theresearch purpose is to define whether the students comprehension ofmathematical concept by applying